2014
DOI: 10.1177/0886260514555126
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Victimization Among College Students With and Without Disabilities

Abstract: Prior research indicates that both college students and individuals with disabilities are at an increased risk of experiencing intimate partner victimization (IPV). However, little is known about IPV risk and its relationship to emotional well-being among the intersection of these two populations. Utilizing a sample of approximately 20,000 college students from the American College Health Association's (ACHA) National College Health Assessment II (NCHA II), this study focuses on this overlooked intersection by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 33 publications
(53 reference statements)
3
33
0
Order By: Relevance
“…9 10 The majority of existing research on the association between disability and IPV comes from the Global North, where evidence, while limited, consistently shows that women with disabilities are at greater risk of IPV than either women without disabilities or men with disabilities. [11][12][13][14][15][16][17][18] A 2012 systematic review and meta-analysis of past 12 months' experience of violence among female and male adults with disabilities identified only five studies that looked at IPV. 11 All were from the USA or Canada and three included only data on mental illness in non-representative samples, from which the authors estimated a pooled OR of 1.78 (95% CI 1.42 to 2.22) for recent IPV among 574 adults with mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…9 10 The majority of existing research on the association between disability and IPV comes from the Global North, where evidence, while limited, consistently shows that women with disabilities are at greater risk of IPV than either women without disabilities or men with disabilities. [11][12][13][14][15][16][17][18] A 2012 systematic review and meta-analysis of past 12 months' experience of violence among female and male adults with disabilities identified only five studies that looked at IPV. 11 All were from the USA or Canada and three included only data on mental illness in non-representative samples, from which the authors estimated a pooled OR of 1.78 (95% CI 1.42 to 2.22) for recent IPV among 574 adults with mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found rates of cyber-bullying among young regular Internet users (between 10 and 17 years old) that range from 4 to 72 % [ 9 , 10 ], and lower rates among college population compared to adolescent samples ranging from 9 to 20 % [ 11 14 ]. Cyber-bullying and cyber-teasing are known to cause higher level of depression disorders in victims that traditional ways of bullying among adolescents [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies show that violence in the lives of people with disabilities usually does not end in childhood but rather continues throughout the life span with intimate partner violence (IPV) being a very frequent phenomenon. Women with disabilities (physical and intellectual) are more likely to be abused by their partners than women without disabilities, and for longer periods of time ( Nosek et al, 2001 ; Smith and Strauser, 2008 ; Hughes et al, 2011 ; Scherer et al, 2014 ). In addition to experiencing subtle forms of abuse that exploit aspects of disability, such as withholding medication or denying needed supports ( Lund, 2011 ), they are also more often victims of severe forms of physical partner violence, including being kicked or punched ( Brownridge, 2006 ).…”
Section: Introductionmentioning
confidence: 99%